Self-Fulfillment of Social Science Theories: Cooling the Fire. (January 2016) - Bergenholtz, Carsten; Busch, Jacob
Self-fulfillment of theories is argued to be a threat to social science in at least two ways. First, a realist might worry that self-fulfillment constitutes a threat to the idea that social science is a proper science consistent with a realist approach that develops true and successful statements about the world. Second, one might argue that the potential self-fulfilling nature of social science theories potentially undermines the ethical integrity of social scientists. We argue that if one accepts that social science theories are not based on laws akin to those that govern natural reality or acknowledges that if one can predict self-fulfillment via a meta-theory that explains the underlying regularities of the self-fulfilling change, the threat to realism is dismantled. Furthermore, on the basis of these arguments, we show that if one is unable to predict the (moral) consequences of a theory, it is difficult to ascribe moral responsibility at the individual level. It is, therefore, not the potential self-fulfillment of theories per se that poses an ethical challenge, in contrast to claims in the literature.